The association of energy and macronutrient intake at breakfast and cardiovascular disease in Chinese adults: From a 14-year follow-up cohort study - Du, Xiaoan; Yang, Ru; Ma, Mengdi; Ke, Songqing; Zheng, Jie; Tan, Xiaodong (Frontiers in Nutrition, 2023)
Background We aimed to examine the associations between energy and macronutrient intakes at breakfast and the incidence of cardiovascular events among Chinese adults. Methods There were 12,937 participants from the China Health and Nutrition Survey who met the study criteria and completed six rounds of questionnaires in 1997, 2000, 2004, 2006, 2009, and 2011. Combined weighing methods with 24-h dietary recall were used to measure dietary intake throughout the day. Intakes of macronutrients at breakfast were calculated using energy provided by nutrients as a percentage of breakfast energy. We calculated hazard ratios using a multivariable Cox frailty model with random intercepts to account for household clustering. Results During follow-up, we documented 453 (3.6 per 1,000 person-years) major cardiovascular events, 195 (1.5 per 1,000 person-years) myocardial infarctions, and 293 (2.3 per 1,000 person-years) strokes. In Chinese adults, more breakfast carbohydrates or less proteins intake was associated with the reduced risk of cardiovascular diseases. Especially for women, higher intake of breakfast carbohydrates was associated with a lower risk of major cardiovascular events (quintile 5 vs. quintile 1, HR 0.47 [95%CI 0.30–0.74]; ptrend = 0.0008) and stroke (quintile 5 vs. quintile 1, HR 0.48 [95%CI 0.26–0.88]; ptrend = 0.0006). Higher intake of breakfast proteins was associated with a higher risk of major cardiovascular events (quintile 5 vs. quintile 1, HR 1.77 [95%CI 1.12–2.79]; ptrend = 0.1162), myocardial infarction (quintile 5 vs. quintile 1, HR 2.49 [95%CI 1.21–5.11]; ptrend = 0.2641). There was a significant association between breakfast fat intake and cardiovascular diseases in the adult population, but less significant correlation was found in Chinese men or women. Breakfast fat intake was positively associated with the risk of major cardiovascular events (quintile 5 vs. quintile 1, HR 1.74 [95%CI 1.27–2.36]; ptrend = 0.0070), myocardial infarction (quintile 5 vs. quintile 1, HR 2.03 [95%CI 1.23–3.37]; ptrend = 0.0168), and stroke (quintile 5 vs. quintile 1, HR 1.64 [95%CI 1.12–2.41]; ptrend = 0.0732). There was a significant reduction in major cardiovascular events and stroke when breakfast energy intake was moderated, even if the independence of skipping breakfast. Conclusion High carbohydrate intake and low protein and fat intake at breakfast may contribute to cardiovascular health while maintaining a moderate energy intake.